CONVERSATIONAL ANALYSIS OF MR. & MRS. SMITH MOVIE SCRIPT IN TERMS OF SPEECH FUNCTIONS AND GRAMMATICAL MOODS TO REVEAL TENOR DIMENSIONS OF THE SPOKEN TEXT - Umi Honey, - (2008)
The study entitled "Conversational Analysis of Mr. & Mrs. Smith Movie Script in terms of Speech Functions and Grammatical Moods to Reveal Tenor Dimensions of the Spoken Text" seeks to illuminate fundamental theory of the grammar of interaction proposed by Halliday (1994) that is adopted by Eggins (2000). Textual analysis applying the form of qualitative social analysis was undertaken for every single clause of the movie script containing twelve (12) scenes. Two (2) scenes were excluded considering the absence of Mr. & Mrs. Smith's private interactions. The research performs 403 typical (unmarked) correlations of all 525 initiating and responding moves showing dominant number up to 76.8 %. It sets forth a proof that the participants commit a role of close and familiar relation of husband and wife which shares equal power, frequent contact, and high affective involvement. Furthermore, the classification analysis of the male character separated from female performed a gender differentiation in the language use. It brought the issue of gender bias involving demeaning portrayal of male and female character representation where power and status relation were necessarily exposed.